The Value of Modified Renal Rim Grade in Predicting Acute Kidney Injury Following Severe Acute Pancreatitis. Issue 5 (September 2018) - Wang, Yi; Cao, Li-kun; Wei, Yi; Song, Bin
Abstract : Objective: To retrospectively determine the value of modified renal rim grade (MRRG) in predicting acute kidney injury (AKI) in the early phase of severe acute pancreatitis (SAP). Methods: This institutional review board–approved retrospective study included patients with SAP who underwent abdominal contrast-enhanced computed tomography (CT) within 48 hours after disease onset. Modified renal rim grade, renal rim grade, CT severity index, modified CT severity index, extrapancreatic inflammation on CT scores, and posterior pararenal (PPR) space involvement were assessed. Clinical data, including bedside index of severity in acute pancreatitis and New Japanese Severity Scoring system scores, were collected. Primary end points were AKI and mortality. Scores were evaluated by receiver operating characteristic curve analysis. Correlational analyses between MRRG scores and the other scores were performed with Spearman analysis. Result: One hundred five consecutive patients were enrolled in our study. The areas under the curve (AUCs) of MRRG in predicting AKI (0.90) and mortality (0.83) were comparable to extrapancreatic inflammation on CT (0.89 and 0.85, P > 0.05) and were higher than those of the other CT scores ( P < 0.05). Modified renal rim grade score of greater than 4 yielded sensitivities and specificities of 81% and 89% for predicting AKI and 88% and 66% for mortality. Modified renal rim grade correlated moderately with bedside index of severity in acute pancreatitis (Spearman r = 0.47) and New Japanese Severity Scoring system ( r = 0.43) scores. Besides, the prevalence of PPR space involvement in nonrecovery AKI patients was higher than that in recovery patients (94% vs 36%, P < 0.05). Conclusions: Modified renal rim grade is well correlated with the occurrence of AKI and mortality in SAP. The PPR space involvement is a promising prognostic factor for nonrecovery of AKI in SAP patients.